Second Five Year Plan: Progress Report 1958-59 - Planning Commission, Government of India (Planning Commission, Government of India, 1960)
Initial administrative problems, reorganisation of States, rise in development costs, rapid depletion of foreign exchange reserves, large budgetary deficits, sharp fall in agricultural output in 1957-58, marked rise in foodgrains prices and the generally inflationary tendency induced by increased developmental expenditure both in the public and private sectors had caused serious stresses and strains in the economy during the initial years of the second plan. With a view to combining development with stability, agricultural programmes were stepped up, fiscal and monetary disciplines were enforced and an appraisal of the internal and external resources of the second plan was undertaken to re-define priorities. The salutary effect of these measures and other favourable factors was felt in the third year of the plan.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Economic Trends and Achievements; Agricultural Programme; Second Five-Year Plan- India